INTEGRASI ASPEK INOVASI DALAM STUDI KELAYAKAN BISNIS UNTUK MENDUKUNG TRANSFORMASI DIGITAL - Intan Pratiwi; Ragil Setyorini; Dwi Astuti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Digital transformation has fundamentally reshaped the business landscape, creating both new opportunities and challenges. In this context, innovation serves as a key factor in supporting business sustainability and competitiveness. However, implementing innovation often involves risks and uncertainties, requiring in-depth analysis through business feasibility studies. This article highlights the importance of integrating innovation into business feasibility studies to support digital transformation. The study explores how innovation can enhance market, financial, operational, and technical analyses within the feasibility process. Using theoretical approaches and case studies, this article demonstrates that integrating innovation can increase the relevance and effectiveness of business feasibility studies in a dynamic technological era. These findings provide strategic guidance for decision-makers to optimize innovation potential, ensure sustainability, and achieve competitive advantage in the digital age.